Long-Term Care Facilities For Older Adults: Spatial Distribution In The Belo Horizonte Metropolitan Area, Minas Gerais, Brazil - Marina Celly Martins Ribeiro de Souza; Natália de Cássia Horta; Maria da Consolação Magalhães Cunha; Quesia Nayrane Ferreira; Tatiana Teixeira Lacerda de Barral; Tatiana Resende Prado Rangel de Oliveira (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVE: To present the geographical distribution and profile of long-term care facilities (LTCFs) for older adults in the Belo Horizonte Metropolitan Area, Minas Gerais, Brazil. METHOD: Data collection was based on secondary sources from five institutions and government departments, followed by an electronic search on websites and blogs, phone calls, and/or on-site visits. A descriptive analysis of the characteristics of the facilities was performed, as well as georeferencing and spatial analysis of Belo Horizonte's LTCFs. The sample consisted of 156 LTCFs in 21 municipalities. RESULTS AND CONCLUSION: There were philanthropic facilities in all the mapped places, and 12 municipalities with smaller populations had only one facility each. There was no record of public facilities. Private LTCFs prevail in large municipalities, which are characterized by an accelerated growth of social facilities. The spatial distribution analysis, compared with the Belo Horizonte's urban life quality index, allowed the discussion of availability of services according to the location of social facilities and the needs of the population, a topic not yet addressed by the municipalities.